2021
DOI: 10.3390/ma14216640
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Friction Stir Welded 2205 Duplex Stainless Steel Butt Joints

Abstract: Friction stir welding (FSW) as a solid-state process is an excellent candidate for high softening temperature materials welding; however, extending the tool life is required to make the process cost-effective. This work investigates the use of a high pin to shoulder ratio (65%) tungsten carbide (WC) tool for friction stir welding of 5 mm thick 2205 DSS to extend the tool life of this low-cost tool material. In addition, the effect of FSW parameters in terms of rotational rates, travel speeds, and downward forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Furthermore, it was reported [ 36 ] that the flash formed on the advanced side (AS) is higher than the retreating side (RS) due to the stirring mechanism during the FSW process, in which the material in the stir zone flows the plasticized material from AS to RS [ 41 ]. Thus, FSW welding variables should be considered to control the formation of an excessive welding flash, including tool design, plunge depth, tilt angle, and introduced heat input [ 42 , 43 ]. Hence, the FSW machine parameters (400 rpm rotation speed, 100 and 400 mm/min travel speeds, 4.8 mm tool plunge depth, and 3° tilt angle) and the FSW tool design should be chosen carefully to reduce flash forming during the welding process of AA5083-H1111.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was reported [ 36 ] that the flash formed on the advanced side (AS) is higher than the retreating side (RS) due to the stirring mechanism during the FSW process, in which the material in the stir zone flows the plasticized material from AS to RS [ 41 ]. Thus, FSW welding variables should be considered to control the formation of an excessive welding flash, including tool design, plunge depth, tilt angle, and introduced heat input [ 42 , 43 ]. Hence, the FSW machine parameters (400 rpm rotation speed, 100 and 400 mm/min travel speeds, 4.8 mm tool plunge depth, and 3° tilt angle) and the FSW tool design should be chosen carefully to reduce flash forming during the welding process of AA5083-H1111.…”
Section: Resultsmentioning
confidence: 99%
“…Since the amounts of temperature and deformation experienced are insufficient to cause dynamic recrystallization, these grains are generated mainly by dynamic recovery [ 53 , 54 ]. Finally, a refined equiaxed grain structure can be seen in the SZ [ 43 , 53 ]. Since the heat generated and plastic deformation are sufficiently high, in contrast to the TMAZ, to induce this phenomenon, the new grain structure is formed by continuous dynamic recrystallization [ 53 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the aerospace sector increasingly relies on recycled aluminum Al to meet its growing demand. In addition, there is a push for development in the materials used, the joining techniques, and the design structure of aircraft [41,141].…”
Section: Future Perspective Of Al In Aerospace Applicationsmentioning
confidence: 99%
“…values. Another recent work on stainless steel based on implementing a high pin to shoulder ratio (65%) tungsten carbide (W.C.) by Ahmed et al [39] concluded that a highly defect-free weld can be generated by optimising rotational rate, travel speed, and downward force parameters.…”
Section: Fsw Of Steelmentioning
confidence: 99%